ANALISIS PENINGKATAN KESIAPAN RADAR PERTAHANAN UDARA DALAM RANGKA MENDETEKSI ANCAMAN REGIONAL TERHADAP WILAYAH IBU KOTA NUSANTARA - Muhammad Fazlur Ansari Jayaratno; Asep Setiawan; Usni Usni; Endang Sulastri (Institut Pemerintahan Dalam Negeri, 2026)
The relocation of the national capital to Ibu Kota Nusantara (IKN) in East Kalimantan places the region in a strategic yet vulnerable position within the Indo-Pacific regional security constellation. Its proximity to ALKI II, the Makassar Strait, and regional rivalries make strengthening the air defense radar system crucial for early detection and enforcing air sovereignty. This study examines the improvement of air defense radar readiness to detect regional threats to IKN, focusing on detection capabilities, radar data integration, and threat anticipation. Using a qualitative approach, data was collected through literature reviews, policy documents, operational reports, and interviews with officials at Koopsudnas and Satrad 205 Balikpapan. The analysis identified strengths, weaknesses, opportunities, and challenges in Kalimantan's radar system. Findings reveal that while the Indonesian Air Force’s radar network detects cooperative and non-cooperative flights, it faces limitations like older technology, vulnerability to electronic warfare, and radar blank spots in northern Kalimantan. Data integration via the Balikpapan MCC is underway, but more coordination with civilian radars and the establishment of a Pontianak MCC are needed for better situational awareness. This study recommends modernizing radar systems, expanding sensor networks, strengthening AI-based data integration, and improving personnel competencies for a robust IKN air defense system.